Meaning-making in response to the traumatic loss of a child. - Chan, Angeline Michell (My University, 2013)
Recent research supports the theoretical premise that healthy forms of bereavement include meaning making as a coping response to loss as well as a move away from Freud’s original postulation regarding the importance of decathexis as necessary to a healthy resolution of grief. However, traumatic bereavement produces particular kinds of difficulties in meaningmaking and the possible resolution of this kind of loss. The study explored responses in relation to the traumatic loss of a child through homicide in a sample of 7 parents (2 couples, 3 mothers) who were identified through the The Compassionate Friends (TCF) chapter in Highlands North, Johannesburg and who volunteered to take part in the study. Semi structured interviews were conducted, recorded, transcribed and subjected to an interpretive thematic content analysis. The thematic content analysis revealed that meaning making responses in relation to the loss of a child through homicide, are complex and that somewhat unexpectedly, parents experienced expectations from society and others to engage in particular kinds of meaning-making as counterproductive and alienating. Issues concerning the simultaneous introjection of and de-cathexis from the lost child also proved enlightening. Meaning-making also involves both some degree of trauma resolution and the recognition of what the loss of the significant other entails. The research also explored the choices and decisions that parents reported as being important in response to the traumatic loss of their child, and therefore suggests some useful pointers for those who encounter traumatically bereaved individuals in the course of their work.
Keywords: Bereavement--South Africa--Psychological aspects.; Grief--South Africa--Psychological aspects.; Loss (Psychology).; Children--South Africa--Death--Psychological aspects.; Violent deaths--South Africa--Psychological aspects.